2016
DOI: 10.1021/acs.nanolett.6b00526
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Single-Crystalline Organic Nanowires on Graphene: Solution-Phase Epitaxy and Optical Microcavities

Abstract: Vertically aligned nanowires (NWs) of single crystal semiconductors have attracted a great deal of interest in the past few years. They have strong potential to be used in device structures with high density and with intriguing optoelectronic properties. However, fabricating such nanowire structures using organic semiconducting materials remains technically challenging. Here we report a simple procedure for the synthesis of crystalline 9,10-bis(phenylethynyl) anthracene (BPEA) NWs on a graphene surface utilizi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 54 publications
0
24
0
Order By: Relevance
“…1 describes the pathway for fabricating oriented nanopillars on pencil-drawn graphite versus the conventional CVD graphene surfaces using a physical vapor transport (PVT) crystallization method. Here, we replaced the graphene 26 , 27 commonly used by scribbling on silicon (Si) wafers using a pencil (graphite bar 8B) purchased from the University of Massachusetts Amherst art store. This pencil-drawn graphite served as the templating interlayer (RMS = 1.94 nm, Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1 describes the pathway for fabricating oriented nanopillars on pencil-drawn graphite versus the conventional CVD graphene surfaces using a physical vapor transport (PVT) crystallization method. Here, we replaced the graphene 26 , 27 commonly used by scribbling on silicon (Si) wafers using a pencil (graphite bar 8B) purchased from the University of Massachusetts Amherst art store. This pencil-drawn graphite served as the templating interlayer (RMS = 1.94 nm, Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The methods for the synthesis of these 1D systems generally rely on three approaches including template procedures, solution-phase deposition, and vapor transport. [2][3][4]6,10,13 Condensation from the vapor phase at low pressure (or simply physical vapor deposition, PVD) counts within the last group and presents interesting features such as (i) direct formation of single crystal nanowires with controlled morphology on different substrates; (ii) high adaptability to a large amount of different π-conjugated small molecules; (iii) high growth rate and controlled density of nanowires with appropriated homogeneity; (iv) solventless and one-step synthesis; and (v) straightforward compatibility with other vacuum deposition and processing methods. 2,14−18 The method consists of the low-pressure sublimation of purely organic or metalorganic small-molecules from the bulk crystals counterpart and their condensation on the surface of diverse supports.…”
mentioning
confidence: 99%
“…Instead of applying solution‐based processing to both 2D materials and organic molecules, solution‐processed organic molecules can be deposited onto large‐area and high‐quality 2D materials grown by CVD . Some previous works have reported that solution‐processed organic thin films tend to orient favorably in a lying‐down, face‐on configuration owing to the vdW interactions and preferred orbital orientation, electronic density, and dipole overlap afforded by 2D materials.…”
Section: Fabrication and Physical Properties Of 2d–organic Hybrid Strmentioning
confidence: 99%
“…Additionally, it has been demonstrated that a 2D template layer can also induce the growth of vertically aligned organic nanowires via a simple solution‐based procedure. The development of highly ordered solution‐processed organic semiconductors is occurring in parallel with the rapid growth of organic optoelectronics …”
Section: Fabrication and Physical Properties Of 2d–organic Hybrid Strmentioning
confidence: 99%